Analisis Korelasi Jaminan Service Level Agreement (SLA) terhadap Kepercayaan Pengguna dalam Mengadopsi Sistem Pembayaran Digital - Muhammad Fasya Palevi; Evy Nurmiati (Journal of Science, Technology, and Innovation, 2026)
The growth of digital payment systems has increased the need for service mechanisms capable of ensuring the quality, security, and reliability of transactions on an ongoing basis. This study aims to analyze the correlation between Service Level Agreement (SLA) guarantees and user trust in adopting digital payment systems. The method used is a Systematic Literature Review (SLR) with a PRISMA approach to literature discussing digital payments, service quality, information security, and technology adoption. The analysis was conducted through thematic synthesis to identify patterns of relationships between SLA dimensions and the formation of user trust. The findings indicate that data security, system reliability, electronic service quality, and policy transparency are the primary SLA dimensions that have a positive correlation with user trust. Trust acts as a mechanism that bridges the influence of service quality on decisions regarding the adoption of digital payment technology. Consistent SLA implementation also contributes to increased satisfaction, loyalty, and sustained service usage. These findings confirm that SLAs serve a strategic function in linking the technical aspects of services with user behavior, thereby becoming a crucial element in supporting the development of a secure, trustworthy, and sustainable digital payment ecosystem.